Decay photons from the axionlike particles burst of type II supernovae - Jaeckel, Joerg; Cavalcanti Malta, Pedro; Redondo, Javier (Physical review, 2018)
We determine limits from SN 1987A on massive axionlike particles with masses in the 10 keV-100 MeV range and purely coupled to two photons. Axionlike particles produced in the core collapse escape from the star and decay into photons that can be observed as a delayed and diffuse burst. We discuss the time and angular distribution of such a signal. Looking into the future, we also estimate the possible improvements caused by better gamma-ray detectors or the explosion of the red supergiant Betelgeuse in a supernova event.
Gesehen am 26.02.2020